The Effect of Additional Composition Substrates on The Rate and Quality of Food Waste Bioconversion by Black Soldier Fly Larvae and Superworm - Hakim, Mohammad Najmi Rafi; Mirwan, Mohamad (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Food waste has become one of the main problems in environmental management in Indonesia. Food waste that is not managed properly can cause groundwater pollution, greenhouse gas emissions, unpleasant odours, and bacterial breeding grounds, for such examples are tofu pulp and expired bread. This research aims to analyze the effect of additional composition of tofu waste and expired bread substrates on the rate and quality of food waste bioconversion by black soldier fly larvae and superworm. The research method used direct experimentation with variations in substrate composition over 12 days (BSF) and 30 days (Superworms). The highest Waste Reduction Index (WRI) was achieved by BSF in the treatment with 60% tofu pulp and 40% expired bread (M4) at 7,65. For Superworm, substrate consisting of food waste and tofu pulp (K2) produced the highest reduction percentage of 63,4% and the Waste Reduction Index (WRI) value of 2,11%. for the final weight and best ECD value for BSF larvae were found on variable M5 consisting of food waste, tofu pulp 50%, and expired bread 50%, with a final weight of 0,3 grams per larva and an ECD value of 16,25%. Variable K2 recorded the highest final weight and ECD value for Superworm, with a final weight of 4,15 grams per larva and an ECD value of 2,94%. The characteristics of the bioconversion residue (frass) from both types of larvae meet the C, N, P, K standards in accordance with SNI 19-7030-2004, the results showed that the combination of tofu pulp and expired bread substrates in treatments M4 and K4 produced residues with a more balanced macro nutrient content, making them the most optimal.